Developing a Comprehensive Psychological Debriefing Program to Enhance the Well-Being of Police Personnel - Diaz Jr, Efren Dela Cruz; Villegas, June Rey A.; Narra, Donald B.; Relatorres, Queen Henyelour S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study conducted an assessment of the well-being of members of the Philippine National Police - City Intelligence Unit of the Cebu City Police Office for the period 2016 to 2021. A quantitative descriptive design was employed, utilizing the Ryff Scale 42 Items, Locus of Control, and General Self-Efficacy Scale to gather data. The majority of personnel were male with a baccalaureate degree, and variations were noted in the number of personnel assigned to each police station. The personnel exhibited relatively high scores on all autonomy sub-scales, while the majority demonstrated either low or moderate levels of self-efficacy. Using the Spearman's correlations, Well-being, locus of control, and self-efficacy were found to be statistically significant at the 0.05 level.". This suggests that there is evidence of a linear relationship between these variables in the data. Based on the findings, a comprehensive psychological debriefing program (CPDP) was recommended to improve the well-being of the personnel. The proposed CPDP was tailored to address the unique needs of each group based on their demographic characteristics and psychosocial profiles. The CPDP aimed to enhance autonomy, personal growth, environmental mastery, positive relations with others, purpose in life, and self-acceptance, as well as to foster a culture of psychological health and wellness within the Philippine National Police Intelligence Unit. The proposed action plan offers valuable insights into the unique needs and challenges of PNP Intelligence Unit Personnel, ultimately leading to a more effective and efficient program.